Biomarcadores bioquímicos em fígado de girinos de rãs-touro, Lithobates catesbeianus, como indicadores biológicos de contaminação aquática - Fernandes, Isabela Ferreira (2020)
Various contaminants can affect the aquatic ecosystem and the organisms that live in it and can interfere with their physiological processes, as they accumulate in different tissues. Therefore, the evaluation of the effects of these contaminants on aquatic organisms contributes to the predictability of the action of different pollutants in this environment, generating information on mechanisms of adaptability to environmental stressors, as they are used as indicators of aquatic contamination. For this purpose, the experimental design consisted of exposing for 96 h bullfrog tadpoles, Lithobates catesbeianus, the water collected from two points (P1 and P2) of the Sorocaba River and in the dry (August and September) and rainy (March) periods. The following parameters were evaluated in the liver: protein concentration (metallothionein - MT, carbonyl proteins - PCO) and (lipid lipoperoxidation - OPL). In addition, the presence of metals, agrochemicals and drugs in the water and sediment at both points of the river were analyzed. In the analysis of water and sediment, the presence of agrochemicals and drugs was not detected; however, the presence of metals was verified at both points and in both periods. The presence of metals significantly increased MT and PCO in the liver of tadpoles exposed to water in P1 and P2 and in the rainy season, while in the dry period, the concentration of PCO and OLP significantly increased in the liver of tadpoles exposed to water from P1 and P2, respectively. These results indicate a picture of oxidative stress by the presence of metals in the water and suggests that these animals were able to alter the metabolic pathways for detoxification processes. Therefore, these results demonstrated that the proposed effect biomarkers can be good indicators of aquatic contamination in bullfrog tadpoles.